A W-Band 3-D Integrated Mini-SAR System With High Imaging Resolution on UAV Platform - Man-Lai Ding; Chi-Biao Ding; Li Tang; Xue-Mei Wang; Jia-Meng Qu; Rui Wu (IEEE Access, 2020)
The light-small multi-rotor unmanned aerial vehicle (UAV) carrying with a mini synthetic aperture radar (SAR) payload has provided an advanced information acquisition technology for the target detecting and imaging fields. In this paper, a W-band compact SAR system is proposed, which has been successfully deployed on the unmanned aerial vehicle (UAV) platform demonstrating state-of-the-art imaging resolution of about 4.5 cm. In order to achieve remarkable compactness, light weight and powersaving feature for the proposed system, the techniques of the three-dimensional (3-D) integration are adopted, where a whole-system size of only 67 × 60×50 mm3 and the weight of 400 g are obtained. This proposed system achieves higher SAR-imaging resolution thanks to the contributions of many efforts, including the technique of high-linearity waveform generation, the substrate integrated waveguide (SIW) antenna with high isolation by the electromagnetic band-gap (EBG) mechanism, and a novel motion compensation method for the imaging formation. To validate this proposed idea, a UAV SAR prototype operating at W-band is designed and fabricated. The measurements show great signal-to-noise ratio imaging results with excellent focusing effect. The proposed SAR system is promisingly an ideal candidate for the target detecting/imaging applications deployed on the UAV platform.